Review of Current International Decision-Making Processes for Newborn Screening: Lessons for Australia - Metternick-Jones, Selina Carolyne; Lister, Karla Jane; Dawkins, Hugh J. S.; White, Craig Anthony; Weeramanthri, Tarun Stephen (Frontiers in Public Health, 2015)
Newborn bloodspot screening has been operating successfully in Australia for almost 50 years. Recently, the development of new technologies and treatments has led to calls for the addition of new conditions to the screening programs. Internationally it is recognized by governments that national policies for newborn screening should support transparent and evidence-based decision-making, and promote consistency between states within a country. Australia is lagging behind the international community, and currently has no national policies or decision-making processes, agreed by government, to support its newborn screening programs. In contrast, New Zealand (NZ), the United Kingdom (UK) and the United States of America (US) have robust and transparent processes to assess conditions for screening, which have been developed by, and have pathways to, government. This review provides detail on the current policy environment for newborn screening in Australia, highlighting that there are a number of risks to the programs resulting from the lack of a decision-making process. It also describes the processes used to assess conditions for newborn screening in the US, UK and NZ. These examples highlight the benefits of developing a national decision-making process, including ensuring that screening is evidence based and effective. These examples also provide models that might